2005
DOI: 10.1177/1056789505048602
|View full text |Cite
|
Sign up to set email alerts
|

Microplane-damage-based Effective Stress and Invariants

Abstract: This paper addresses some issues of the application of the effective stress tensor to coupled damage-plasticity from the point of view of a microplane. In this paper, damage and effective stress are defined on microplanes. The effective stress tensor of Murakami (1988) can be recovered as the second-order fabric tensor of the effective stress vector. The effective second invariantJ J 2 is defined as the integration of the square of the effective shear stress over the unit sphere. It is revealed that theJ J 2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…3 J II (σ) (e.g., Fung 1965, p.80). Here the author took notice of the proportionality between the spherical average of square shear stress magnitude and J II (e.g., Yang et al 2005):…”
Section: Exact Physical Meaningmentioning
confidence: 99%
“…3 J II (σ) (e.g., Fung 1965, p.80). Here the author took notice of the proportionality between the spherical average of square shear stress magnitude and J II (e.g., Yang et al 2005):…”
Section: Exact Physical Meaningmentioning
confidence: 99%
“…This article is essentially an extension of the work by Yang et al (2005a) who deal with this issue from a viewpoint of effective stress vectors of Kachanov (1958) and Rabotnov (1963). Yang et al (2005a) have shown that the well-known second-order effective stress tensor of Murakami (1988) can be viewed as the second-order fabric tensor of the Kachanov-Rabotnov effective stress vector. Therefore, it seems meaningful to develop higherorder effective stress tensors to characterize highly anisotropic damage states of materials.…”
Section: Introductionmentioning
confidence: 96%
“…To provide better insight into the physical mechanism while adhering to the basic framework of continuum damage mechanics, microplane models based on geometric damage were proposed to separate the independent effect of geometrical characteristic . In these models, the concept of effective stress and the hypothesis of strain equivalence were reformulated on the microplane level, and geometric damage variables could be defined on the microplanes so as to represent a different reduction of the net stress‐carrying area fraction in different directions, which is impossible in tensorial models.…”
Section: Introductionmentioning
confidence: 99%
“…By defining a single damage variable on microplanes as an orientation distribution function (ODF) and an effective stress vector on the microplanes, and assuming static constraint between macro nominal stresses and microplane nominal stresses, Yang et al . showed that the second‐order effective stress tensor of Murakami can be recovered as the second‐order fabric tensor of the effective stress vector. Furthermore, they proved that the anisotropic yield criteria of damaged materials whose matrix follows von Mises and Drucker–Prager yield criteria possess the form of the famous Hill criterion and its extension by Liu to pressure‐sensitive materials , in which the parameters are related to the fabric tensors of the microplane damage variable.…”
Section: Introductionmentioning
confidence: 99%